STRATEGI PENGEMBANGAN MUSEUM RADYA PUSTAKA GUNA MENINGKATKAN DAYA TARIK WISATA DI KOTA SURAKARTA - Heri Kristanto; Yustina Denik R; Dyah Palupiningtyas (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2023)
Radya Pustaka Museum is said to be the oldest museum in Indonesia. Radya Pustaka Museum is currently experiencing a setback in terms of tourist visits. This is due to two things, namely; 1. Pull factors or from the museum side, (collection, arrangement, promotion, interior design, interpretation, digitization). 2. Driving factors or from the visitor's side, (motivation drops, shifts in interest, lack of references). This study aims to determine the potential of the Radya Pustaka Museum as a tourist destination, along with efforts to develop the area into an integrated tourist destination. This research was conducted using a qualitative method in the Sriwedari Park area in general and the Radya Pustaka museum in particular. Data collection techniques were carried out by observations, interviews and document studies. Based on the results of data collection, it can be concluded that: (1) the Radya Pustaka Museum has the potential to be used as a cultural tourism destination, (2) a tourism attraction and tourist attraction development strategy is needed, (3) a tourism and regional development strategy is needed as well as good marketing support.